Some Reflections on the Evaluation of Expert Systems in Medicine - Fieschi, M.; Joubert, M. (Methods of Information in Medicine, 1986)
Several examples are given to underline the difficulties of evaluating expert systems in order to demonstrate that in the medical domain in particular their routine applications have not yet been developed to a great extent.
Keywords: Expert Systems; Artificial Intelligence; Evaluation